2007
DOI: 10.1016/j.neuroscience.2007.06.046
|View full text |Cite
|
Sign up to set email alerts
|

A high soy diet reduces programmed cell death and enhances bcl-xL expression in experimental stroke

Abstract: Soy phytoestrogens have been proposed as an alternative to estrogen replacement therapy and have demonstrated potential neuroprotective effects in the brain. We have shown that a high soy diet significantly reduces infarct size following permanent middle cerebral artery occlusion (MCAO). Here, we tested the hypothesis that a high soy diet would attenuate programmed cell death after stroke. Adult female Sprague-Dawley rats were ovariectomized and fed either an isoflavone-reduced diet (IFP) or a high soy diet (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…Dietary isoflavones have been shown in rats to improve stroke outcome after transient focal cerebral ischemia, as indicated by smaller infarct volume and improved neurological status ( 3 ). A decrease in apoptotic rate in the cerebral cortex accompanies the decrease in brain infarct size conferred by a soybeanenriched diet in rats subjected to MCAO ( 6 ). In vitro experiments have confirmed that apoptosis is a potential target of soybean isoflavones, because genistein prevents glutamate-and thapsigargin-induced apoptosis in embryonic cerebral cortical cell cultures ( 15 -17 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dietary isoflavones have been shown in rats to improve stroke outcome after transient focal cerebral ischemia, as indicated by smaller infarct volume and improved neurological status ( 3 ). A decrease in apoptotic rate in the cerebral cortex accompanies the decrease in brain infarct size conferred by a soybeanenriched diet in rats subjected to MCAO ( 6 ). In vitro experiments have confirmed that apoptosis is a potential target of soybean isoflavones, because genistein prevents glutamate-and thapsigargin-induced apoptosis in embryonic cerebral cortical cell cultures ( 15 -17 ).…”
Section: Discussionmentioning
confidence: 97%
“…Dietary soybean, which is rich in isoflavaones, decreases stroke injury in both female and male rats ( 4 ) and the soybean isoflavone genistein confers neuroprotection in a mouse cerebral ischemia model ( 5 ). Importantly, dietary supplementation with soybean decreases apoptotic rate in the cerebral cortex of rats subjected to MCAO ( 6 ). However, the molecular mechanisms underlying these beneficial effects of isoflavones in the central nervous system are unknown ( 7 , 8 ).…”
mentioning
confidence: 99%
“…The improvement of neurologic outcome by genistein has been reported in a model of ischemia in mice [54]. The isoflavones of dietary soy have improved stroke outcome in male rats following ischemia [20,[55][56][57]. The increase in neurologic score can occur through ICP decrease [25,28].…”
Section: Discussionmentioning
confidence: 99%
“…Both ovariectomized female and male rats on a high soy diet show a significant reduction in infarct size, neurological deficit, and cerebral apoptosis following transient or permanent middle cerebral artery occlusion (Schreihofer et al, 2005;Burguete et al, 2006;Lovekamp-Swan et al, 2007a;Castello-Ruiz et al, 2011). The addition of the soy isoflavones genistein or equol to the diet has similar protective effects in both sexes (Ma et al, 2010;Castello-Ruiz et al, 2011;Qian et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Because soy isoflavones have properties of phytoestrogens and can bind and activate estrogen receptors, these protective effects are likely to include those implicated in estrogen-dependent neuroprotection. Like estrogens (Dubal et al, 1999;Alkayed et al, 2001;Won et al, 2006), dietary soy isoflavones enhance the expression of antiapoptotic members and inhibit pro-apoptotic members of the Bcl-2 family of proteins (Bu and Lephart, 2005;Lovekamp-Swan et al, 2007a). Similarly, both estrogens (Razmara et al, 2008;Zhang et al, 2009) and soy isoflavones (Ma et al, 2010(Ma et al, , 2013Qian et al, 2012) reduce oxidative stress in response to cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%